Porous aluminum electrodes with 3D channels and zig-zag edges for efficient hydrogen evolution. Issue 38 (12th April 2019) - Periasamy, Arun Prakash; Sriram, Pavithra; Chen, Yu-Wen; Wu, Chien-Wei; Yen, Ta-Jen; Chang, Huan-Tsung
Abstract : A porous aluminum electrode formed through base and acid treatments, and anodization exhibits improved electro- and photo-electrocatalytic activity for hydrogen production. Abstract : An eco-friendly electrochemical approach, including base and acid treatments, and anodization, has been developed for preparation of defect-rich porous aluminum electrodes for efficient hydrogen evolution. A small Tafel slope value of 43 mV dec −1 reveals improved reaction kinetics through the micropores, 3D channels, and zig-zag edges of the aluminum electrode. It exhibits an onset potential of 460 mV and an overpotential of 580 mV at the current density of 10 mA cm −2 due to the porous and edge structures that enhance the charge transfer and mass transport.